PEMBUATAN GAS BIO DARI BEBERAPA MACAM LIMBAH BIOMASSA PADAT DENGAN CARA "BATCH CULTURE" - Gusmailina Gusmailina; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1988)
A  laboratory  experiment    on  biogas generation  using solid  waste  in a  batch  culture  under  Thermophillic condition was conducted at the Forest Products Research  and  Development  Centre, Bogor.The solid  waste used in the experiment were rice straw, water hyacinth (Eichornia  crassipes Mart.  Solms)  and rubber wood  (Hevea  braziliensis)  sawdust.Fermentation   condition   for  biogas production   was kept  constant  under  temperature  of 53°C  for 8 days.  Inoculumn used for  fermentation  was  residue from the experiment of  organic municipal solid  waste fermentation.The raw material used in this experiment consisted  of mixture  of  73 gram rice straw and 27 gram water, 70 gram rice straw and  30 gram  water  hyacinth, 38 gram rubber  wood  sawdust  and  62 gram water,  36,25  gram rubber wood  sawdust and  63,75 water hyacinth. To each mixture   was added  900 gram  of  starter  with  dry  matter  content  28%. Each substrate sample   was  then  placed   in  a  1,5 littre  digester.The  result  of  the  experiment   indicates  that  the highest  production   of biogas and methane  were produced   from  rice straw  substrate (0,43  littre  of biogas and 0,21 littre of methane  per gram of straw respectively),  and the efficiency   of biogas produced  was 75%.The   total   calorific value of   biogas   produced was  lower  than   that  obtained   from  direct burning  of  rice straw.  Although    the  calorific  value   of   biogas   is  relatively  low, its  burning  quality is better compared   with direct  burning. Besides that, the residue from  fermentation   process  could  be utilized  as organic fertilizer  and mushroom  media.